Inefficient lock-in and subsidy competition - Rainald Borck; Hyun-Ju Koh; Michael Pflüger (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2009)
This paper shows that subsidy competition may be efficiency enhancing. We model a subsidy game among two asymmetric regions in a new trade model, where capital can freely move among regions, but capital rewards are repatriated. We study subsidy competition, starting from an equilibrium where the industry core is ineffi- ciently locked in to the smaller region. When regions weigh workers' and capitalists' welfare equally, the core region will set its subsidy low enough that the industry re- locates to the larger region, restoring an efficient allocation. When workers' welfare is weighted more heavily, the core may pay subsidies that are high enough to prevent a relocation of industry.
Keywords: F12; F15; H25; H73; R12; 330; agglomeration; asymmetric regions; subsidy competition; Welfare